DETERMINAN FINANCIAL DISTRESS PADA PERUSAHAAN SUB SEKTOR PERDAGANGAN RITEL DI BEI - Yafet Yuliyanto (2022)
This quantitative study aims to examine and determine the effect of profitability, liquidity, cash flow, firm size and gross domestic product on financial distress. The population used in this study are retail trading sub-sector companies listed on the Indonesia Stock Exchange for the period 2018 to 2020. The sampling technique used is purposive sampling with certain criteria, so that it is determined that there are 24 retail companies studied in this study. The data in this study are secondary data. Data analysis in this study used the logistic regression method. The results of this study indicate that liquidity have an effect on financial distress, while profitability, cash flow, firm size and gross domestic product have no effect on financial distress.